Cluster‐based modularization of processes recovered from web applications. Issue 2 (20th September 2010) - Di Francescomarino, Chiara; Marchetto, Alessandro; Tonella, Paolo; Ferenc, Rudolf; Knodel, Jens; Winter, Andreas
SUMMARY Web applications are often used to expose business processes implemented as software systems. This paper describes a technique for recovering business processes based on a dynamic analysis of the applications behavior. The technique described here does not require any access to internal software artifacts of the application, such as source code or documentation. An initial process is inferred to by means of the analysis of execution traces, in which the execution of GUI elements such as forms and links is recorded. The recovered process is then abstracted by clustering its elements according to four different criteria: structural, page‐based, dependency‐based and semantical. A case study has been conducted with the aim of evaluating understandability and readability of the reverse engineered processes as well as the clustering techniques used in refining them. Copyright © 2010 John Wiley & Sons, Ltd.